Doping and transformation mechanisms of Fe3+ ions in Fe-doped TiO2. Issue 7 (3rd February 2017) - Yang, Yajun; Yu, Yanlong; Wang, Jingsheng; Zheng, Wenjun; Cao, Yaan
Abstract : The doping mechanisms, phase transition and ultrasonic piezoelectric catalytic activity for reduction of CO2 of Fe-doped TiO2 are investigated. Abstract : A series of Fe-doped TiO2 samples with different concentrations of Fe 3+ ions annealed at different temperatures were prepared using a sol–gel method. For Fe-doped TiO2, the existing states of Fe 3+, the transformation of these existing states and the phase transition are investigated. It is revealed that the existing states of Fe 3+ and the transformation of these existing states (substitutional Fe 3+, α-Fe2 O3 and Fe2 TiO5 ) are closely related to the annealing temperature and the concentration of Fe 3+ . The anatase–rutile (A–R) transition is promoted by the substitutionally doped Fe in the TiO2 lattice. In addition, the Fe-doped TiO2 with a high calcination temperature (800 °C) and high doping concentration ( x > 20) shows obvious ultrasonic piezoelectric catalytic activity for the reduction of CO2 to CH4 . This work may be useful in understanding the doping mechanisms of Fe-doped TiO2, and the fabrication of new catalytic materials.